PENGGUNAAN MODEL PEMBELAJARAN QUANTUM TEACHING DENGAN MEDIA KONKRET DALAM PENINGKATAN PEMBELAJARAN IPA SISWA KELAS IV SDN SINGOYUDAN TAHUN AJARAN 2013/2014 - SASONGKO, JONI (KALAM CENDEKIA PGSD KEBUMEN, 2018)
Abstract: The Application Of Quantum Teaching Model With Concrete Media To Improving Science Learning In IV Grade State Elementary School Singoyudan. This research aims to: describe the using of quantum teaching model with concret media in science learning of four grade students, to improve csience learning, and to describe obstacle and solution of quantum teaching model with concrete media. The subjects were students in the IV grade State Elementary School Singoyudan which consists of 18 students. Data collection techniques is observation, interviews, and achievement test. Validate data is triangulation of data sources and technique. The results that the using of Quantum Teaching model with Concrete Media in increasing science learning of IV grade State Elementary School Singoyudan. Keywords: Quantum Teaching, Media Concrete, Science Learning Abstrak: Penggunaan Model Pembelajaran Quantum Teaching dengan Media Konkret dalam Peningkatan Pembelajaran IPA Siswa Kelas IV SDN Singoyudan. Penelitian ini bertujuan mendeskripsikan penggunaan model pembelajaran Quantum Teaching dengan Media Konkret dalam peningkatan pembelajaran IPA siswa kelas IV SD, meningkatkan pembelajaran IPA, dan mendeskripsikan kendala serta solusi dari penggunaan model pembelajaran Quantum Teaching dengan Media Konkret. Subjek penelitian siswa kelas IV SDN Singoyudan sejumlah 18 siswa. Teknik pengumpulan data adalah tes, observasi, dan wawancara. Validitas data adalah triangulasi sumber dan teknik. Hasil penelitian bahwa penggunaan model pembelajaran Quantum Teaching dengan Media Konkret, dapat meningkatkan pembelajaran IPA siswa kelas IV SDN Singoyudan. Kata kunci: Quantum Teaching, Media Konkret, Pembelajaran IPA